Teknologi Pengolahan Beras Analog Berbahan Dasar Tepung Pati dan Kacang Kacangan Dalam Upaya Meningkatkan Diversifikasi Pangan : Review - Ahmad Hadi Yustianto; Heny Kusumayanti (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Indonesia is a country that consumes rice as a staple food. The figure for the value of rice consumption in Indonesia itself is very different from the figure for rice production from Indonesian farmers, this causes Indonesia to often import rice to meet the need for the staple food staple rice. So a solution is needed in the form of verified food without having to change the habits of Indonesian people in consuming rice, in this case food diversification is needed in the form of analog rice. Analog rice is a processed food that resembles rice but is made from non-rice food ingredients such as beans and tubers, with characteristics similar to rice in shape, texture, and nutritional content that is equal to or exceeds the nutritional content of white rice. Tubers and legumes have enormous potential for application in making analog rice.